Detection of silent infection of severe acute respiratory syndrome coronavirus 2 by serological tests - Nishimura, Masashi; Sugawa, Satoshi; Ota, Shinichiro; Suematsu, Etsuko; Shinoda, Masahiro; Shinkai, Masaharu (PLOS ONE, 2022)
To control COVID-19 pandemic is of critical importance to the global public health. To capture the prevalence in an accurate and timely manner and to understand the mode of nosocomial infection are essential for its preventive measure. We recruited 685 healthcare workers (HCW's) at Tokyo Shinagawa Hospital prior to the vaccination with COVID-19 vaccine. Sera of the subjects were tested by assays for the titer of IgG against S protein's receptor binding domain (IgG (RBD)) or IgG against nucleocapsid protein (IgG (N)) of SARS-CoV-2. Together with PCR data, the positive rates by these methods were evaluated. Overall positive rates among HCW's by PCR, IgG (RBD), IgG (N) with a cut-off of 1.4 S/C (IgG (N)1.4), and IgG (N) with a cut-off of 0.2 S/C (IgG (N)0.2) were 3.5%, 9.5%, 6.1%, and 27.7%, respectively. Positive rates of HCW's working in COVID-19 ward were significantly higher than those of HCW's working in non-COVID-19 ward by all the four methods. Concordances of IgG (RBD), IgG (N)1.4, and IgG (N)0.2 against PCR were 97.1%, 71.4%, and 88.6%, respectively. By subtracting the positive rates of PCR from that of IgG (RBD), the rate of overall silent infection and that of HCW's in COVID-19 ward were estimated to be 6.0% and 21.1%, respectively. For the prevention of nosocomial infection of SARS-CoV-2, identification of silent infection is essential. For the detection of ongoing infection, periodical screening with IgG (RBD) in addition to PCR would be an effective measure. For the surveillance of morbidity in the population, on the other hand, IgG (N)0.2 could be the most reliable indicator among the three serological tests.